OP0047 Fdg-pet scan investigations in vasculitis, other than giant cell arteritis or polymyalgia rheumatica. (1st June 2001) - Blockmans, DE; Maes, A; Stroobants, S; Bobbaers, H; Mortelmans, L
Abstract : Background: An increased 18-fluoro-deoxyglucose (FDG) uptake has been described in the large vessels of the thorax and legs in patients with giant cell arteritis (GCA) and/or polymyalgia rheumatica (PMR), 1, 2 using positron emission tomography (PET). This reflects increased glucose metabolism in these inflamed vessels. Objectives: We wanted to expand the FDG-PET technology to other patients with biopsy-proven vasculitis. We wondered if vasculitis could also be visualised in patients with other types of large vessel vasculitis, in patients with medium-sized vessel vasculitis and in patients with different forms of small vessel vasculitis. Methods: Patients with biopsy-proven vasculitis, different from GCA/PMR, who were admitted to the General Internal Medicine Department of the University Hospital Gasthuisberg, Leuven, Belgium underwent FDG-PET scan before eventual treatment with steroids was started. One hour before imaging, 6.5 Mbq/kg FDG were injected intravenously. Results: A total of 18 patients were included: 2 patients had large vessel vasculitis (1 Takayasu's arteritis, 1 periaortitis), 3 patients had medium-sized vessel inflammation (2 Churg-Strauss syndrome, 1 polyarteritis nodosa or PAN) and 13 patients had small vessel vasculitis (7 Wegener's granulomatosis, 2 Henoch-Schönlein purpura, 2 cutaneous polyarteritis, 1 relapsing polychondritis and 1 microscopic polyangiitis). Aortic FDG-uptake was very intense in periaortitis and rather discrete, but persistent under steroid treatment in Takayasu's arteritis. There was no increased vascular FDG-uptake in patients with PAN or Churg-Strauss syndrome. Increased FDG-uptake in the lungs was seen in Wegener's granulomatosis patients with lung involvement, as well as in the patient with microscopic polyangiitis and lung involvement. Cutaneous involvement of the legs in small vessel vasculitis is also reflected on FDG-PET scan, as well as bowel involvement in Henoch-Schönlein purpura. (Para) nasal involvement in Wegener's granulomatosis also produces a hot focus on FDG-PET scan. Conclusion: Apart from GCA/PMR, FDG-PET scan can also be used to visualise the inflamed thoracic arteries in those other – but much less frequent – large vessel vasculitides as there are  Takayasu's arteritis and periaortitis. In medium-sized vasculitis, FDG-PET scan seems to be of much less value. In small vessel vasculitis, internal organ involvement can be visualised, especially in the lungs. However, FDG-PET scan can not distinguish pulmonary vasculitic involvement from pulmonary infection, since both conditions induce more local FDG metabolism. References: Blockmans, et al . New arguments for a vasculitic nature of polymyalgia rheumatica using positron emission tomography. Rheumatology 1999;38:444–7 Blockmans, et al . Positron emission tomography in giant cell arteritis and polymyalgia rheumatica: evidence for inflammation of the aortic arch. Am J Med. 2000;108:246–9